2013
DOI: 10.1097/qad.0b013e32835fac51
|View full text |Cite
|
Sign up to set email alerts
|

Tubular and glomerular proteinuria in HIV-infected adults with estimated glomerular filtration rate ≥60 ml/min per 1.73 m2

Abstract: This study distinguished risk factors for tubular injury, mainly related to HIV disease and its treatment (tenofovir), and glomerular injury, linked to non HIV-related variables (age, diabetes, hypertension). Measuring uPCR, uACR and uAPR may help with the detection and specific management of early chronic kidney disease in HIV-infected patients having normal or sub-normal eGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…We observed that the prevalence of glomerular and tubular proteinuria in our sample was close, 7.9 and 10.8%, respectively. This frequency of glomerular proteinuria is in accordance with other published data [4,5,12,31,32]. Studies that have attempted to evaluate glomerular and tubular proteinuria simultaneously during HIV infection are however scarce in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that the prevalence of glomerular and tubular proteinuria in our sample was close, 7.9 and 10.8%, respectively. This frequency of glomerular proteinuria is in accordance with other published data [4,5,12,31,32]. Studies that have attempted to evaluate glomerular and tubular proteinuria simultaneously during HIV infection are however scarce in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that have attempted to evaluate glomerular and tubular proteinuria simultaneously during HIV infection are however scarce in the literature. Interestingly, Reynes et al [5] found similar results with an estimated frequency of proteinuria of 18.2% among patients with eGFR ≥60 mL/min/1.73 m 2 and among them, 50.7% had an albumin to protein ratio <0.4, and this was an indication of the presence of tubular proteinuria. In light of the relationship between the type of proteinuria and glomerular filtration, we found in our study that patients with a glomerular or tubular proteinuria had lower eGFRs at the beginning of each period compared to patients without proteinuria.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Reynes et al [21] cross-sectionally evaluated the frequency of proteinuria, uAPR, and kidney tubular dysfunction in HIV-infected patients with normal estimated glomerular filtration rate and found TDF use was associated with increased tubular proteinuria and low uAPR. Samarawickrama et al [12] evaluated uAPR in HIV-infected patients and found that 12% of those receiving TDF therapy had tubular proteinuria, defined as uPCR more than 30 mg/mmol (265 mg/g creatinine) with uAPR less than 0.4.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade proteinuria is common in patients on antiretroviral therapy, and determining acceptable cutoffs in this population is an area requiring further study [21,23]. Additionally, it is necessary to determine the test characteristics of the uAPR in all HIV-infected patients who have proteinuria and undergo kidney biopsy.…”
Section: Discussionmentioning
confidence: 99%